Microvascular decompression of the trigeminal nerve in the treatment of SUNCT and SUNA. Issue 9 (12th May 2010) - Williams, Max; Bazina, Renata; Tan, Leong; Rice, Hal; Broadley, Simon A
Abstract : Background: Medical management of short-lasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT) syndrome and short-lasting unilateral neuralgiform headache attacks with cranial autonomic symptoms (SUNA) is often unsatisfactory. Methods: The authors report nine cases of SUNCT/SUNA that failed medical treatment and had an aberrant arterial loop either in contact with or compressing the appropriate trigeminal nerve demonstrated on MRI. All underwent microvascular decompression of the ipsilateral trigeminal nerve for intractable pain. Results: Immediate and complete relief of SUNCT and SUNA symptoms occurred in 6/9 (67%) cases. This was sustained for a follow-up period of 9–32 months (mean 22.2). In 3/9 (33%) cases, there was no benefit. Ipsilateral hearing loss was observed in one case. Conclusion: Medically intractable SUNCT and SUNA subjects with a demonstrable aberrant arterial loop impinging on the trigeminal nerve on neuroimaging may benefit from microvascular decompression.